Photoionization of atom by intense laser fields / Ho Wai Loon - Ho, Wai Loon (2014)
This research is devoted to a detailed study of the interaction between atom and intense laser field, which mainly focusing on the photoionization spectra of hydrogenlike atom. The main theoretical model which is involved in order to describe the photoionization phenomenon is Keldysh’s model. Firstly, the Keldysh’s formalism is derived in details and its physical significance is explored. We have presented the extension of the Keldysh’s theory further into a semianalytical expression to study the characteristics of ionization rate of atom by intense lasers. In particular, the generalization of Keldysh’s model is obtained for linear polarized light from small photoelectron momentum to arbitrary value of momentum. By applying different type of the laser field, i.e. linear, circular and elliptical, we have shown the variation of spectrum of the ionization rate and compare the features of the exact rates with Keldysh analytical result as functions of frequency and electric field strength. Next, the Keldysh’s model is further extended in order to describe the photoionization of hydrogenlike atom from arbitrary initial energy level, which is not only restricted to the initial ground state energy level. A general analytical expression for arbitrary n00 energy level is obtained where n is the principal quantum number. Meanwhile, semianalytical expression is obtained for arbitrary nlm energy level where l is the azimuthal quantum number and m is the magnetic quantum number. Furthermore, we have also extended the Keldysh’s theory to study the interaction between the hydrogenlike atoms with ultra intense laser where the relativistic effect is taken consideration in the model. The extension of the theoretical model into relativistic regime will provide a significant insight into the real world study since experimental works are deal with highly intense pulsed laser such as Ti:Sa laser for research study. The theory developed in this research will particularly benefit the future development of attoseconds laser, thus providing new tools for imaging and requiring further the development of electron control through intense light-matter interaction.